Evidence-Informed Update of Argentina's Health Benefit Package: Application of a Rapid Review Methodology. (11th March 2022) - Alcaraz, Andrea; Alfie, Verónica; Gonzalez, Lucas; Virgilio, Sacha; Garcia-Marti, Sebastián; Augustovski, Federico; Pichon-Riviere, Andrés
Abstract: Objectives: Argentina has a fragmented healthcare system with social security covering almost two thirds of the population. Its benefit package—called compulsory medical program (PMO; by its Spanish acronym Programa Médico Obligatorio )—has not been formally and widely updated since 2005. However, laws, clinical practice guidelines (CPGs), and a high-cost technology reimbursement fund complement it. Our objective was to comprehensively review such a PMO and propose an update considering the corresponding complementary sources. Methods: We followed four steps: (i) identification of health technologies from the current PMO and complementary sources, (ii) prioritization, (iii) assessment through rapid health technology assessment (HTA), and (iv) appraisal and recommendations. We evaluated three value domains: quality of evidence, net benefit, and economics, which were summarized in a five-category recommendation traffic-light scale ranging from a strong recommendation in favor of inclusion to a strong recommendation for exclusion. Results: Eight hundred fifty technologies were identified; 164 of those, considered as high priority, were assessed through rapid HTAs. Those technologies mentioned in laws and CPGs were mostly outpatient essential medicines, whereas those from the reimbursement system were mostly high-cost drugs; of these 101 technologies, 50 percent were recommended to be kept in the PMO. The other 63 (identified by the Superintendence of Health Services, technology producers, and patients) were mostly medical procedures and high-cost drugs; only 25 percent of those resulted in a favorable recommendation. Conclusions: A methodology based on four clearly identified steps was used to carry out a comprehensive review of an outdated and fragmented benefit package. The use of rapid HTAs and a traffic-light recommendation framework facilitated the deliberative evidence-based update.